(untitled) (Proceedings of International Conference on Special Education, 2017)
This qualitative study through observation using experimental method in a form of case study was carried out on three year 2 special remedial pupils who faced difficulty in writing and had low performance in academic. The pupils underwent pre test and post test by copying at near point a piece of simple sentence that contained four words and 20 letters. After the pre test, pupils used Qalamiy for five weeks to support the formation of their dynamic tripod pencil grip and later improve their hand writing. Handwriting assessment was done based on the procedure from the Mcmaster Handwriting Assessment Protocol 2nd Edition (2009). Comparison was made by looking at the type of pencil grip and quality of handwriting based on letter formation characteristics, frequency in erasing and rewriting the letters, balance and thickness of lines of letters, distance between words and between letters, letter size balance and correct spelling. Findings showed the use of Qalamiy could help formation of mature pencil grip and increased the quality of handwriting in terms of balancing the distance between letters as well as distance between words and also the size of the letters. The results of this study can give knowledge to teachers to focus on the aspect of pencil grip, assess the quality of handwring and also implement research-based intervention as an option in addressing the issue of language literacy especially handwriting.